Tightening and loosening of bolted joint - Tanra, Ivan (2013)
Tightness of the bolted joint is main concern in designing a joint. Proper tightness of the bolted joint is needed to prevent failure of the joint due to external disturbance such as vibration. In this project, study of tightness and loosening of bolted joint is done with the usage of DC motor and 2x2 transduction matrix. The transduction matrix explains the relationship of electrical input energy (voltage and current) and mechanical output energy (torque and rotation speed) of the DC motor. Thus, it enables the in-process measurement of mechanical output of the DC motor from its electrical input. The DC motor is used to tighten the bolted joint and measure the mechanical output given to the bolted joint. Based on the measurement result, the tightness and dynamic system modelling of the bolted joint are obtained and study. The relationship between tightness of the bolted joint and its system properties is explained. Lastly, the relationship between the system properties and loosening of the bolted joint under transverse vibration is studied.